Study of thermoelectric magnetohydrodynamic convection on solute redistribution during laser additive manufacturing. Issue 1 (May 2020) - Kao, A; Gan, T; Tonry, C; Krastins, I; Pericleous, K
Abstract: Melt pools formed in laser additive manufacturing (AM) are subject to large thermal gradients, resulting in the formation of thermoelectric currents due to the Seebeck effect. When in the presence of an external magnetic field, a Lorentz force is formed which drives fluid flow in the melt pool. This Thermoelectric Magnetohydrodynamics (TEMHD) phenomenon, can have a significant impact on the melt pool morphology and can alter the microstructural evolution of the solidification process. By coupling steady-state mesoscopic melt pool calculations to a microscopic solidification model, predictions of the resulting microstructure for multiple deposited layers have been obtained. The results indicate that the magnetic field can have a transformative effect on the microstructure and solute redistribution. This study highlights the theoretical potential for using magnetic fields as an additional control system to tailor AM microstructures.